2020
DOI: 10.1016/j.cell.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Protein Structure, Molecular Affinities, and Principles of Cell-Cell Recognition

Abstract: The ability of cells to organize into multicellular structures in precise patterns requires that they ''recognize'' one another with high specificity. We discuss recent progress in understanding the molecular basis of cell-cell recognition, including unique phenomena associated with neuronal interactions. We describe structures of select adhesion receptor complexes and their assembly into larger intercellular junction structures and discuss emerging principles that relate cell-cell organization to the binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
128
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 100 publications
4
128
1
Order By: Relevance
“…This screen reported over 80 new PPIs, including a previously unknown immunoglobulin superfamily (IgSF) PPI network between members of the Dpr and DIP subfamilies. Since we reported the Dpr-DIP network, functional studies have revealed that this network mediates neuronal wiring decisions in the fly brain and neuromuscular system (for review, see Honig and Shapiro, 2020;Sanes and Zipursky, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This screen reported over 80 new PPIs, including a previously unknown immunoglobulin superfamily (IgSF) PPI network between members of the Dpr and DIP subfamilies. Since we reported the Dpr-DIP network, functional studies have revealed that this network mediates neuronal wiring decisions in the fly brain and neuromuscular system (for review, see Honig and Shapiro, 2020;Sanes and Zipursky, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…5B). Interplay between cis and trans interactions are essential for the formation of clusters of adhesion proteins leading to cell-cell recognition 78 . One canonical example is the formation of adherens junction by the clustering of cadherins for which both cis and trans interactions are required 79,80 .…”
Section: The Tm Helices Of Other Receptors Such As Egfrs and Ephas DImentioning
confidence: 99%
“…Over the past few decades, great progress has been made to uncover large families of adhesion proteins that are candidates for cell-surface identity codes for neuronal circuit assembly, such as neurexins [1], olfactory receptors [2], cadherins and families of other adhesion molecules [3][4][5][6]. For example, in Drosophila melanogaster, 38,016 isoforms of Dscam1 (Down syndrome cell adhesion molecule 1)-generated by alternative splicing-endow each neuron with a unique identity code to discriminate self from non-self [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It is this cytoskeletal remodeling that leads to the many functions of Pcdh such as neuronal migration, neurite morphogenesis, dendritic selfavoidance, axonal projection, spine elaboration, synaptogenesis, and neuronal connectivity. We refer interested readers to other excellent reviews discussing various aspects of the clustered Pcdh genes [5,6,[19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%